Anti-Metaphysical Readings of Tractatus Logico-Philosophicus. - Tarai, Ashoka Kumar (Problems / Problemos, 2021)
This paper discusses certain anti-metaphysical readings of Tractatus Logico-Philosophicus. The metaphysical and anti-metaphysical readings can be divided on the interpretations of textual fidelity. The anti-metaphysical readings can be differentiated in taking into account two different understandings with regard to Wittgenstein's pronouncement of nonsense in Tractatus. One is the logical positivists' understanding of nonsense and the other is the resolute reading of the text that emerged as an opposite to the orthodox or standard reading. The aim of discussing these anti-metaphysical readings is to highlight whether a metaphysical reading is possible.